Respuesta :
Answer:
the answer to number one is (13.3,2)
the answer to number two is (2,-2)
Step-by-step explanation:
1. -5+y=-3
3x-8y=24
5+2=-3
3x40/3 -8x2 =24
-3=-3
24=24
(x,y) = (40/3, 2)
2. -3x-4y=2
x+2y=-2
-3(-2-2y) -4y=2
y=2
x=-2-2x(-2)
x=2
(x,y) (2.-2)
-3x2-4x(-2) =2
2+2 x(-2) =-2
2=2
-2=-2
(2,-2)
hope this helps:)
3x-8y=24
5+2=-3
3x40/3 -8x2 =24
-3=-3
24=24
(x,y) = (40/3, 2)
2. -3x-4y=2
x+2y=-2
-3(-2-2y) -4y=2
y=2
x=-2-2x(-2)
x=2
(x,y) (2.-2)
-3x2-4x(-2) =2
2+2 x(-2) =-2
2=2
-2=-2
(2,-2)
hope this helps:)